MECHANISMS OF HEPATITIS B VIRUS PERSISTENCE AND IMMUNE EVASION IN THE LIVER (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article delves into the etiology, mechanisms of development, prevalence, types, clinical implications, and consequences of chronic Hepatitis B Virus (HBV) infection. HBV is a significant global health challenge due to its unique ability to persist and evade the immune system, often resulting in lifelong infection and severe liver disease.